The formation of âruminal bypass proteinâ (in vitro) by adding tannins isolated from Calliandra calothyrsus leaves or formaldehyde - Wina, Elizabeth; Abdurohman, Dindin (Indonesian Animal Sciences Society, 2005)
Ruminal bypass proteinâ is one of the strategies to increase the amount of protein, which enters abomasum and hence, increases ruminant productivity. One of the strategies to obtain âruminal bypass proteinâ is by complexing tannin or formaldehyde with protein. Two experiments were conducted. The first experiment aimed to obtain the optimum level of added tannins to decrease the dry matter digestibility of protein sources. Tannins were isolated from Calliandra calothyrsus leaves. Tannins were added at the level of 0, 10, 20, 30, 40 and 50 mg to each in vitro tube containing 0.5 g of protein source (gliricidia leaves, soybean meal or casein) and the tubes were incubated for 48 hours. The result showed that the optimum level of tannin was 60 mg/g of gliricidia leaves or casein and 80 mg/g of soybean meal. The second experiment aimed to compare the ability of tannin to formaldehyde to form complex with protein. One set of tubes containing tannin-protein or formaldehyde-protein complex was incubated with rumen liquor for 48 h and another set was incubated with rumen liquor (48h) and followed by pepsin-HCl for 24 h (total incubation time: 72 h). After incubation at 48 h or 72 h, the dry matter or protein digestibility of tannin-protein complex was much higher than those of formaldehyde-protein complex. The amount of ruminal bypass protein was almost similar between the two agents to complex gliricidia leaves (34.4 and 32.1 g/100g for tannin-gliricidia and formaldehyde-gliricidia, respectively). Tannin-soybean meal interaction produced 27.9 g/100 g of âruminal bypass proteinâ, which was half of that from reaction between formaldehyde and soybean meal (54.1 g/100 g). Tannin-casein complex was easily broken down in the rumen so that âruminal bypass proteinâ from this complex was very small. It can be concluded that the ability of tannin to form âruminal bypass proteinâ depends on the type of protein source but is the same with the ability of formaldehyde to bind forage protein (Gliricidia sepium). Further feeding evaluation of these tannin-protein complexes is warranted. Â Â Key Words: Ruminal Bypass protein, Calliandra calothyrsus, Tannin, Formaldehyde